Lateral Semi-sitting Position: A Novel Method of Patient's Head Positioning in Suboccipital Retrosigmoid Approaches - Velho, Vernon (Asian J Neurosurg, 2019)
BACKGROUND: The most common methods of positioning patients for suboccipital approaches are the lateral, lateral oblique, sitting, semisitting, supine with the head turn, and park bench. The literature on the positioning of patients for these approaches does not mention the use of lateral semisitting position. This position allows utilization of the benefits of both semisitting and lateral position without causing any additional morbidity to the patient. AIMS: The aim of the present study is to highlight the advantages of the lateral semisitting position while operating various cerebellopontine angle (CPA) and posterior fossa lesions. MATERIALS AND METHODS: The position involved placing the patient in a lateral position with torso flexed to 45° and head tilted toward opposite shoulder by 20°. The most common approach taken was retrosigmoid suboccipital craniotomy. RESULTS: The advantages of lateral semisitting position were early decompression of cisterna magna, and the surgical field remained relatively clear, due to gravity-assisted drainage of blood and irrigating fluid. We could perform all the surgeries without the use of any retractors. The position allowed better delineation of surrounding structures resulting in achieving correct dissection plane and also permitted early caudal to cranial dissection of tumor capsule, thereby increasing chances of facial nerve preservation. Importantly, there is less engorgement of the cerebellum as the venous outflow is promoted. We have not experienced any increased rate of complications, such as venous air embolism, tension pneumocephalus with this lateral semisitting position. CONCLUSIONS: Lateral semisitting position is a relatively safe modification, which combines the benefits of semisitting and lateral position, and avoids the disadvantages of sitting position in operating CPA tumors. This position can provide quick and better exposure of the CPA without any significant complications.